Amazon S3 cookbook : over 30 hands-on recipes that will get you up and running with Amazon Simple Storage Service (S3) efficiently /: over 30 hands-on recipes that will get you up and running with Amazon Simple Storage Service (S3) efficiently. (2015) - Hashimoto, Naoya
No abstract available